Prasugrel Plus Aspirin Beyond 12 Months Is Associated With Improved Outcomes After Taxus Liberté Paclitaxel-Eluting Coronary Stent Placement. Issue 1 (6th January 2015) - Garratt, Kirk N.; Weaver, W. Douglas; Jenkins, Ronald G.; Pow, Thomas K.; Mauri, Laura; Kereiakes, Dean J.; Winters, Kenneth J.; Christen, Thomas; Allocco, Dominic J.; Lee, David P.
Abstract : Background—: The TAXUS Liberté Post Approval Study (TL-PAS) contributed patients treated with TAXUS Liberté paclitaxel-eluting stent and prasugrel to the Dual Antiplatelet Therapy Study (DAPT) that compared 12 and 30 months thienopyridine plus aspirin therapy after drug-eluting stents. Methods and Results—: Outcomes for 2191 TL-PAS patients enrolled into DAPT were assessed. The DAPT coprimary composite end point (death, myocardial infarction [MI], or stroke) was lower with 30 compared with 12 months prasugrel treatment (3.7% versus 8.8%; hazard ratio [HR], 0.407; P <0.001). Rates of death and stroke were similar between groups, but MI was significantly reduced with prolonged prasugrel treatment (1.9% versus 7.1%; HR, 0.255; P <0.001). The DAPT coprimary end point, stent thrombosis, was also lower with longer therapy (0.2% versus 2.9%; HR, 0.063; P <0.001). MI related to stent thrombosis (0% versus 2.6%; P <0.001) and occurring spontaneously (1.9% versus 4.5%; HR, 0.407; P =0.007) were both reduced with prolonged prasugrel. MI rates increased within 90 days of prasugrel cessation after both 12 and 30 months treatment. Composite Global Utilization of Streptokinase and Tissue Plasminogen Activator for Occluded Coronary Arteries (GUSTO) moderate or severe bleeds were modestly increased (2.4% versus 1.7%; HR, 1.438; P =0.234) but severe bleeds were not more frequent (0.3% versus 0.5%; HR, 0.549; P =0.471) in the prolonged treatment group. Conclusions—: Prasugrel and aspirin continued for 30 months reduced ischemic events for the TAXUS Liberté paclitaxel-eluting stent patient subset from DAPT through reductions in MI and stent thrombosis. Withdrawal of prasugrel was followed by an increase in MI after both 12 and 30 months therapy. The optimal duration of dual antiplatelet therapy with prasugrel after TAXUS Liberté paclitaxel-eluting stent remains unknown, but appears to be >30 months. Clinical Trial Registration—: URL: http://www.clinicaltrials.gov . Unique identifier: NCT00997503. Abstract : Supplemental Digital Content is available in the text.